Validation of the Exercise Health Belief Model Scale (EHBMS) Among Indonesian Students - Soetomo, Febryan Steward; Setya Murti, Heru Astikasari (Faculty of Psychology, Universitas Diponegoro, 2026)
The level of physical activity participation among Indonesian university students remains relatively low, despite the proven benefits of exercise for physical and mental health. To better understand students’ beliefs about exercise, a conceptually and culturally appropriate measurement tool is needed. This study aims to adapt and evaluate the validity and reliability of the Exercise Health Belief Model Scale (EHBMS) into the Indonesian language. The adaptation process followed the guidelines of Beaton et al. (2000), including preparation, forward translation, synthesis, back translation, expert judgment, pre-test, and submission. Content validity was assessed using Aiken’s V method, while construct validity was evaluated through Confirmatory Factor Analysis (CFA). Reliability was examined using Cronbach’s Alpha coefficient. A total of 500 university students from various higher education institutions in Indonesia participated through convenience sampling. The analysis showed that the EHBMS-ID instrument possesses strong psychometric properties, with content validity indices ranging from 0.95-1.00, acceptable model fit (RMSEA = 0.078; SRMR = 0.061; CFI = 0.932; TLI = 0.923; GFI = 0.990; NFI = 0.912), item discrimination indices between 0.373-0.830, and a Cronbach’s Alpha reliability coefficient of 0.860. Therefore, the EHBMS-ID is a valid and reliable instrument for measuring university students’ beliefs about exercise behavior in Indonesia.